Inclusive Design Guidance: External Autonomous Vehicle Interfaces. (December 2020) - Roundtree, Karina A.; Hattrup, Steven; Swaminathan, Janani; Zerbel, Nicholas; Klow, Jeffrey; Shitole, Vivswan; Fallatah, Abrar; Khanna, Roli; Adams, Julie A.
Autonomous vehicles are expected on roads in the near future and need to interact safely with external road users, such as manual motor drivers, cyclists, and pedestrians. The particular needs of the external road users, such as children, adults, older adults, and individuals with visual, auditory, and/or cognitive impairments, will vary greatly and must be considered in order to design effective inclusive interfaces for all users. Current interface designs lack effective communication between an autonomous vehicle and external road users with regard to conveying and understanding the mobility intent of each party. The goal is to provide inclusive design guidance for an external human-vehicle interface that enables effective communication between autonomous vehicles and external road users. Factors related to communicating intent, the external road users, and environmental constraints, were used to inform the design guidance.